Initial investigations of coil heat exchanger utilizing waste heat from air conditioning system - Joanna Wilk; Robert Smusz (Advances in Mechanical and Materials Engineering, 2017)
In this paper the selected results of testing of tube coil heat exchanger have been presented. The investigated heat exchanger is designed to preheating domestic warm water with the use of waste heat from air conditioning system. The tested device consists of finned tube coil heat exchanger immersed in the thermal storage tank. The tank is equipped with three heating coils and the cylindrical-shaped temperature stratification system. Two coils use water as a heating medium. The third, double-wall heat exchanger coil is filled with the refrigerant from the air conditioning system. The industrial stand enables the experimental investigations of thermal and flow characteristics of the exchanger. In the paper the authors present the technological scheme of the test stand, specification of components of the stand, research possibilities and the exemplary results of characteristic temperature and pressure measurements.